1991
DOI: 10.1159/000186277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Renal Function in Patients with Moderate Impairment of Renal Function Compared to Normal Men

Abstract: The renal excretory and haemodynamic responses to sustained moderate exertion were investigated in normotensive humans with impaired renal function and normal volunteers. The heart rate increase with exercise was similar in each group. Subjects with impaired renal function showed a significant fall in glomerular filtration rate on exertion, while normals did not. In the presence of renal disease, urine osmolality did not rise with exertion, although it rose markedly in the normal group. Free water clearance be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
5

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
1
9
0
5
Order By: Relevance
“…Taverner et al [18] found that among subjects performing 30 min of aerobic exercise on a cycle ergometer, post-exercise HR was higher in pre-dialysis CKD patients than in control subjects. The authors limited the intensity of the exercise by not allowing subject's HR to exceed 110 bpm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taverner et al [18] found that among subjects performing 30 min of aerobic exercise on a cycle ergometer, post-exercise HR was higher in pre-dialysis CKD patients than in control subjects. The authors limited the intensity of the exercise by not allowing subject's HR to exceed 110 bpm.…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical exercise can improve cardiovascular function [16][17][18] , being beneficial for the treatment of various chronic diseases [18] , including hypertension and the primary and secondary prevention of coronary atherosclerosis [16] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, exercise has been reported to result in a transient fall in glomerular filtration rate and fluid retention in humans with CKD (111). However, these exerciseinduced alterations do not appear to exacerbate preexisting renal dysfunction.…”
Section: Effect On Renal Functionmentioning
confidence: 99%
“…On the morning of study the patient had no breakfast and refrained from caffeine and alcohol. Via an antecubital vein, inulin and para-aminohippurate (PAH) were infused for the measurement of renal clearances according to a standard protocol (Taverner et al, 1991). Subjects were given an oral water load of 200 ml at the start of the study and 100 ml every 0.5 h thereafter.…”
Section: Methodsmentioning
confidence: 99%